MEDIASI DALAM PENYELESAIAN SENGKETA MALADMINISTRASI OLEH OMBUDSMAN - Dyah Adriantini Sintha Dewi (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2014)
Mediation is one of way to solve mal adaministration, that places Ombudsman as a mediator, then eutral side ,to help them get win-win solution. Aproblem that solved during mediation is which concerned with society in which the re must be adeal between them .Aconclution of mediation, is agreement but there isn't block reconciliation to be done. If there conciliationisn't agreed Ombudsman would close the case immedietly with recommendation. Recommendation will be arranged if here were disagreement among them. The task of Ombudsman is not only deal with agreement mediation, but also monitoring next step. Ombudsman will escort and beeye witness inrealization the case. Ombudsman will declare it is done when the case performed and then they will report to President / Parliament if it is not.